Medical students observing a primary care consultation: does student gender affect patient consent?. Issue 1 (2nd January 2023) - Charman, Oliver; Forty, Elizabeth; Hassoulas, Athanasios
ABSTRACT: Clinical placement is an important aspect of undergraduate education in the United Kingdom (UK) but with no national curriculum for primary care teaching, it is important to consider the learning opportunities afforded to students when on these rotations. In earlier years, observing consultations constitutes a large proportion of student experience, with patient consent an integral aspect of this teaching method. This study investigated whether patients consider the gender of a medical student when granting consent for their primary care appointment to be observed and whether this was conditional based on their presenting complaint. In total, 551 adult participants (420 females and 131 males) residing in the UK, aged 18–87 years, responded to an online questionnaire. In total, 229 (41.6%) participants stated that they would be influenced by the student's gender when consenting to observation, notably if the presenting complaint concerned an intimate area or their sexual health. A statistically significant correlation was revealed for consent, participant age and participant gender, with younger female respondents less likely to consent to observation by male students. The findings highlight a potential concern pertaining to equal opportunities between medical students based on gender, with inclusivity and diversity considerations for medical schools and clinicians.